Translation and the Passage to Politics in Contemporary Palestinian Art - Rahman, Najat (Intermédialités / Intermediality, 2012)
Analyzing connections between art and politics, this article proposes that contemporary Palestinian art is a space of dissent that challenges consensus and creates new visions of belonging and new forms of subjectivity. It considers the way the installations and videowork of Mona Hatoum and Till Roeskens and translation in the poetry of Suheir Hammad bring together reflections on “subjective mapping.” Both subjective mapping and translation are shown to imply a passage to politics. The crossing of languages, genres and media in these different artworks therefore establishes an intermedial dialogue—not only between the artworks themselves, but also between subjective mapping and translation, visual art and poetry.